An Uprighting Sprıng Desıgn To Erupt Impacted Second Molar: A Case Report - Cenk Doruk; Oral Sökücü (Galenos Yayinevi, 2003)
Second molar impaction is difficult to treat and the treatment is even more problematic if the second molar is in oblique or horizontal position with the crown tilted mesially or toward the root of maxillary first molar. In this case report we showed an uprighting spring made of TMA that inserted to removable appliance to erupt impacted maxillary second molar. The spring was activated routinly in every appointment. The second molar was uprighted and the appliance was removed at the end of the 3rd month. Five months later the impacted tooth was in occlusion by mastication. This appliance is advantageous because it is effective, simple and acting rapidly.